(untitled) (Journal of actual problems of jurisprudence, 2019)
The article deals with theoretical views on the interpretation of the concept of religious extremism, its constituent elements studied the problem of determining concretized explain the essence of religious extremism.Deals with the study of objects and subjects of extremism.Particular attention is paid to the spread of extremism in Kazakhstan and measures to counter it. Provides recommendations for further improvement of the criminal law in the fight against extremism in the Republic of Kazakhstan. Key words: extremism, the identity of an extremist, religious extremism, confession, creed, criminal law.